SIFAT PROTEKSI EKSTRAK AIR PANAS TEH {Camellia sinensis (L.) Kuntze} HIJAU PADA KHAMIR Candida tropicalis YANG DIPERLAKUKAN DENGAN PARACETAMOL - Julistiono, Heddy (BERITA BIOLOGI, 2011)
In order to develop yeast Candida tropicalis as a model cell for evaluation of substance having anti- or pro-oxidant activity in cell level, the effect of hot water tea {Camellia sinensis (LJ Kuntze) extract on peroxidized lipids, a marker of oxidative stress and cell mortality in the yeast caused by paracetamol has been evaluated. Incubation of yeast cell in the presence of 1.38 % green tea for 2 h decreased cell viability followed with increasing of peroxidized lipids, whereas 0.27 % green tea caused increasing of peroxidized lipids without causing cell death.Yeast cell was not affected by 0.1 % green tea. Incubation of yeast cell with presence of 0.15 % (g/v) paracetamol for 2 h did not cause cell mortality, however content of peroxidized lipids increased significantly. In the presence of higher dose of paracetamol (0.3 %) cell viability remarkably decreased and followed with increasing of peroxidized lipids significantly. Green tea of 0.1 % increased cell viability of cells treated with 0.3 % paracetamol while peroxidised lipids decreased. The data indicated that high dose of paracetamol caused oxidative stress in yeast cells, while green tea with lower concentration might protect paracetamol toxicity due to its antioxidant property. Although the antioxidant property, high dose of green tea could cause oxidation due to its pro-oxidant activity. In conclusion, yeast C. tropicalis could be potentially used as a model cell to evaluate substances having antioxidant property in cell level.